2008
DOI: 10.1179/174313208x300413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of large dose hyperbaric oxygenation therapy on prognosis and oxidative stress of acute permanent cerebral ischemic stroke in rats

Abstract: (1) The two protocols of large dose hyperbaric oxygenation therapy are highly efficient in reducing infarct volume and improving neurobehavioral outcome in permanent MCAO rats within the earliest stages of stroke; (2) increased duration of hyperbaric oxygenation therapy does not appear to equate to improved outcomes; in fact, the longer duration may aggravate the oxidative stress in ischemic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…, lipid peroxidation and protein oxidation were prevented, although the enzyme activities were similarly stimulated. Several experimental studies have demonstrated accumulation of tissue oxidative damage after HBO [13,[23][24][25], but only few have investigated the effects of NBO. Studies in which effects of short periods (1-2 h) of NBO were investigated show that hyperoxia does not increase oxidative stress and/or affects antioxidant activity [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…, lipid peroxidation and protein oxidation were prevented, although the enzyme activities were similarly stimulated. Several experimental studies have demonstrated accumulation of tissue oxidative damage after HBO [13,[23][24][25], but only few have investigated the effects of NBO. Studies in which effects of short periods (1-2 h) of NBO were investigated show that hyperoxia does not increase oxidative stress and/or affects antioxidant activity [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The 10% homogenate made as described before was also used here for MDA assay and diluted with saline for the determination of SOD activity. Activity of SOD in hippocampus was measured by the method reported using nicotinamide adenine denucleotide reduced form as a substrate [30]. The SOD activity was expressed as units/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…Research showed that the oxygen therapy was neuroprotective when started either during ischemia,5051 as early as 10 minutes,52 25 minutes,53 40 minutes,5455 60 minutes,56 90 minutes,57 or 180 minutes after MCAO 5859606162. Our previous study proved that delayed HBOT 48 hours after permanent MCAO (pMCAO) can still convey neuroprotection and restorative cell proliferation 63.…”
Section: Key Points Of Efficient Co-administration Of Hbot and R-tpamentioning
confidence: 97%